Surface modification of probiotics via metabolic labeling - Du, Yulin (Nanyang Technological University, 2024)
Click chemistry reactions, especially those between alkynes and azides, are renowned for their rapid reaction rates, high atom economy, and product selectivity. Hence, the azide- alkyne cycloaddition reaction represents the core of click chemistry. Particularly, strain- promoted azide-alkyne cycloaddition (SPAAC) reactions do not require metal catalysts or high temperature conditions and achieve high efficiency and selectivity in cycloaddition reactions through a strain-promoted mechanism. This lays the foundation for the application of click chemistry in biological systems. In this study, based on the incorporation mechanism of D-amino acids in cell wall synthesis, we successfully achieved azide modification on the surface of probiotics, enabling the probiotic surface to undergo click chemistry reactions with DBCO-modified Au plasmonic blackbody (AuPB) and thereby expanding its potential applications in the biomedical field. AuPB exhibits favorable biocompatibility and its hyperbranched structure affords it a wide range of localized surface plasmon resonances (LSPR), enabling effective absorption of light energy from UV to near-infrared spectra and exhibiting significant photothermal effects. Utilizing the natural localization ability of probiotics, AuPB can be targeted to specific regions, such as Streptococcus mutans in the oral cavity or tumor cells within the body where its photothermal effects can be used to precisely kill targeted bacteria or cells. This forges a new avenue for biomedical research and treatment.